A model-based assessment of the potential use of compound-specific stable isotope analysis in river monitoring of diffuse pesticide pollution - S. R. Lutz; H. J. van Meerveld; M. J. Waterloo; H. P. Broers; B. M. van Breukelen (Hydrology and Earth System Sciences, 2013)
Compound-specific stable isotope analysis (CSIA) has, in combination with model-assisted interpretation, proven to be a valuable approach to quantify the extent of organic contaminant degradation in groundwater systems. CSIA data may also provide insights into the origin and transformation of diffuse pollutants, such as pesticides and nitrate, at the catchment scale. While CSIA methods for pesticides have increasingly become available, they have not yet been deployed to interpret isotope data of pesticides in surface water. We applied a coupled subsurface-surface reactive transport model (HydroGeoSphere) at the hillslope scale to investigate the usefulness of CSIA in the assessment of pesticide degradation. We simulated the transport and transformation of a pesticide in a hypothetical but realistic two-dimensional hillslope transect. The steady-state model results illustrate a strong increase of isotope ratios at the hillslope outlet, which resulted from degradation and long travel times through the hillslope during average hydrological conditions. In contrast, following an extreme rainfall event that induced overland flow, the simulated isotope ratios dropped to the values of soil water in the pesticide application area. These results suggest that CSIA can help to identify rainfall-runoff events that entail significant pesticide transport to the stream via surface runoff. Simulations with daily rainfall and evapotranspiration data and one pesticide application per year resulted in small seasonal variations of concentrations and isotope ratios at the hillslope outlet, which fell within the uncertainty range of current CSIA methods. This implies a good reliability of in-stream isotope data in the absence of transport via surface runoff or other fast transport routes, since the time of measurement appears to be of minor importance for the assessment of pesticide degradation. The analysis of simulated isotope ratios also allowed quantification of the contribution of two different reaction pathways (aerobic and anaerobic) to overall degradation, which gave further insight into the transport routes in the modelled system. The simulations supported the use of the commonly applied Rayleigh equation for the interpretation of CSIA data, since this led to an underestimation of the real extent of degradation of less than 12% at the hillslope outlet. Overall, this study emphasizes the applicability and usefulness of CSIA in the assessment of diffuse river pollution, and represents a first step towards a theoretical framework for the interpretation of CSIA data in agricultural catchments.